History of life suport - Patryk Rzońca; Maja Chrzanowska-Wąsik; Mariusz Goniewicz; Kamil Bednarz; Grzegorz Nowicki (Kazimierz Wielki University, 2017)
Since the beginning of time the human being could not accept the inevitability of death, yet religious dogma and tradition undermined the possibility to fight it. Instructions for how resuscitation should be practiced has significantly changed over decades. The given paper presents the review of the literature concerning the history of the development of life support.